Consumer Behavior in Sharia Economic Perspective: Theory and Practice Study - Mukhtar Adinugroho; Reizano Amri Rasyid; Riyan Sisiawan Putra; Mokhamad Ramadani Ilham Akbar; Teguh Herlambang (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2023)
Islam sees economic activity as one way to accumulate and increase the reward for falah (happiness of the world and the hereafter). The motive for consuming in Islam is basically mashlahah, needs and obligations. Satisfaction of a Muslim is not based on market more or less items that can be consumed, but based on how religious values ​​are obtained from what it does. In the teachings of the Islamic religion for the purpose of consumption is the biggest maslahah, so that he can achieve victory in duina and hereafter. Satisfaction in Islam includes consumer satisfaction and creative satisfaction, consumer satisfaction will produce the ready creation of satisfaction, because the consumption made by a Muslim will give his physical strength, so he can be more creative. To measure the satisfaction of a Muslim we can use the concept of conventional utilities.